Postoperative GH and Degree of Reduction in IGF-1 Predicts Postoperative Hormonal Remission in Acromegaly - Cardinal, Tyler; Collet, Casey; Wedemeyer, Michelle; Singer, Peter A.; Weiss, Martin; Zada, Gabriel; Carmichael, John D. (Frontiers in Endocrinology, 2021)
Purpose: Determine predictive factors for long-term remission of acromegaly after transsphenoidal resection of growth hormone (GH)-secreting pituitary adenomas. Methods: We identified 94 patients who had undergone transsphenoidal resection of GH-secreting pituitary adenomas for treatment of acromegaly at the USC Pituitary Center from 1999-2019 to determine the predictive value of postoperative endocrine lab values. Results: Patients underwent direct endoscopic endonasal (60%), microscopic transsphenoidal (38%), and extended endoscopic approaches (2%). The cohort was 63% female and 37% male, with average age of 48.9 years. Patients presented with acral enlargement (72, 77%), macroglossia (40, 43%), excessive sweating (39, 42%), prognathism (38, 40%) and frontal bossing (35, 37%). Seventy-five (80%) were macroadenomas and 19 (20%) were microadenomas. Cavernous sinus invasion was present in 45%. Available immunohistochemical data demonstrated GH staining in 88 (94%) and prolactin in 44 (47%). Available postoperative MRI demonstrated gross total resection in 63% of patients and subtotal resection in 37%. Most patients (66%) exhibited hormonal remission at 12 weeks postoperatively. Receiver operating characteristic (ROC) curves demonstrated postoperative day 1 (POD1) GH levels ≥1.55ng/mL predicted failure to remit from surgical resection alone (59% specificity, 75% sensitivity). A second ROC curve showed decrease in corrected insulin-like growth factor-1 (IGF-1) levels of at least 37% prognosticated biochemical control (90% sensitivity, 80% specificity). Conclusion: POD1 GH and short-term postoperative IGF-1 levels can be used to successfully predict immediate and long-term hormonal remission respectively. A POD1 GH cutoff can identify patients likely to require adjuvant therapy to emphasize clinical follow-up.